Pengaruh Implementasi Indeks Literasi Zakat Terhadap Strategi Pengumpulan Zakat di BAZNAS Provinsi Jawa Barat: Pengaruh Implementasi Indeks Literasi Zakat Terhadap Strategi Pengumpulan Zakat di BAZNAS Provinsi Jawa Barat - Nirma Bhakti Fertiwi (Muttaqien, 2024)
In the previous study, the discussion of zakat collection was only based on material aspects and social welfare. It also measures zakat literacy at the national and provincial levels. However, studies that precisely measure elements of the zakat literacy index in BAZNAS West Java Province still need to be completed. Therefore, the Zakat Literacy Index is used to measure the level of community literacy in the West Java Province BAZNAS management area for the Zakat collection strategy. This study aims to determine the level of the Zakat Literacy Index in BAZNAS West Java Province. It was knowing the zakat collection strategy at BAZNAS West Java Province to maximize the potential of zakat. The research method of the Zakat Literacy Index using the Zakat Literacy Index framework that has been published by the Center for Strategic Studies of the Amil Zakat Agency (PUSKAS BAZNAS) consists of three stages, namely the calculation of the Zakat Literacy Index for BAZNAS of West Java Province, the grouping of problem priorities using SWOT Analysis.Furthermore, the SWOT matrix functions as an analytical tool in determining solutions to make it easier to formulate a solution strategy based on the results of interviews with experts and academics. The study results showed that the measurement of Zakat Literacy in BAZNAS West Java Province received an index value of 75.07, and it was included in the medium or moderate category of the number of respondents involved, as many as 129. The External and Internal Factors Evaluation Matrix describes that BAZNAS West Java Province has superior strengths to weaknesses and relatively more significant opportunities than obstacles. Obstacles in collecting zakat include the understanding (literacy) of zakat, which is still low among the public, socialization about zakat centered on ASN, and public distrust of the transparency and accountability of zakat institutions.